A Robust PID Autotuning Method for Steam/Water Loop in Large Scale Ships. Issue 4 (2018) - Zhao, Shiquan; Ionescu, Clara M.; De Keyser, Robin; Liu, Sheng
Abstract: During the voyage of the ship, disturbances from the sea dynamics are frequently changing, and the ship's operation mode is also varied. Hence, it is necessary to have a good controller for steam/water loop, as the control task is becoming more challenging in large scale ships. In this paper, a robust proportional-integral-derivative (PID) autotuning method is presented and applied to the steam/water loop based on single sine tests for every sub-loop in the steam/water loop. The controller is obtained during which the user-defined robustness margins are guaranteed. Its performance is compared against other PID autotuners, and results indicate its superiority.